PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA YANG BERDAMPAK PADA KINERJA DOSEN POLITEKNIK ATMI SURAKARTA - Dewi Kartikasari (STIE St. Pignatelli Surakarta, 2018)
The purpose of this study are to examine and analyze the influence of Leadership, Work Environment, Competence And Organizational Culture To Job Satisfaction That Impact Lecturer Performance At Polytechnic ATMI Surakarta.This study is a survey research. The data used are primary data by sampling of lecturer at Polytechnic ATMI Surakarta as many as 57 respondents. The data analysis method was tested by validity, reliability test, t-test, F, coefficient of determination (R2) and path analysis test.T test results as follows: leadership not significant effect on job satisfaction, work environment significant effect on job satisfaction, competence significant effect on job satisfaction, organizational culture not significant effect on job satisfaction, leadership not significant effect on performance, the working environment have a significant effect on performance, competence significantly influence the performance, organizational culture not significant effect on the performance, satisfaction significant effect on the performance of work. F test results showed simultaneous variables of leadership, work environment, competence, organizational culture and job satisfaction have a significant effect on the performance of lecturers. Results Analysis The coefficient of determination (R2) shows that 77.7% of faculty performance variation can be explained by the leadership, work environment, competence, organizational culture and job satisfaction while the remaining 22.3% is explained by other factors outside the model. The result of path analysis showed a direct influence on the performance of greater competence than the indirect effect on performance competence through job satisfaction. The direct effect on the performance of the work environment is greater than the indirect effect on the performance of the work environment through job satisfaction. The direct effect on the performance leadership is smaller than the indirect effect of leadership on performance through job satisfaction. The direct effect on the performance organizational culture is smaller than the indirect effect of organizational culture on performance through job satisfaction. Based on the results of total leverage to improve performance would be more effective if through increased competence.